2013
DOI: 10.1016/j.cryobiol.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cryoprotectant agents on spermatogenesis efficiency in cryopreserved and grafted neonatal mouse testicular tissue

Abstract: Restoration of male fertility associated with use of the cryopreserved testicular tissue would be a significant advance in human and animal assisted reproductive technology. The purpose of this study was to test the effects of four different cryoprotectant agents (CPA) on spermatogenesis and steroidogenesis in cryopreserved and allotransplanted neonatal mouse testicular tissue. Hank's balanced salt solution (HBSS) with 5% fetal bovine serum including either 0.7 M dimethyl sulfoxide (DMSO), 0.7 M propylene glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…Travers et al (2011) reported that using 1.5 M DMSO as CPA had high cell viability in the cryopreservation of immature mouse testis tissue. Yildiz et al (2013) reported that DMSO could effectively prevent the formation of ice crystals with a tetrahedral structure and provided a greater protection against freezing with regard to testicular survival rates in the grafted samples compared to PrOH, EG, and glycerol. In this study, the optimal concentrations of DMSO, PrOH, glycerol, and sucrose were 10, 10, 7.5, and 10 % (P <0.05), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Travers et al (2011) reported that using 1.5 M DMSO as CPA had high cell viability in the cryopreservation of immature mouse testis tissue. Yildiz et al (2013) reported that DMSO could effectively prevent the formation of ice crystals with a tetrahedral structure and provided a greater protection against freezing with regard to testicular survival rates in the grafted samples compared to PrOH, EG, and glycerol. In this study, the optimal concentrations of DMSO, PrOH, glycerol, and sucrose were 10, 10, 7.5, and 10 % (P <0.05), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…After the cryopreservation of testicular tissue, detecting the content of testosterone can be used to evaluate of the survival of the tissue (Keros et al, 2007;Curaba et al, 2011;Gouk et al, 2011). Yildiz et al (2013) reported that the DMSO group had similar serum testosterone levels to fresh grafted controls, while serum testosterone levels were significantly lower in the PrOH, EG, and glycerol groups. The results of previous studies, using DMSO for in vitro endocrine and partial exocrine functions in both human (Keros et al, 2005(Keros et al, , 2007 and mouse immature testes (Milazzo et al, 2008), were similar to Yildiz et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference between the CPAs in terms of DNA fragmentation. YILDIZ et al (2013); however, observed higher cell viability and preservation of tissue structure with DMSO when comparing these four CPAs in the slow freezing of testicular fragments from mice.…”
Section: Cryoprotectant Agentsmentioning
confidence: 99%
“…The protocol by YILDIZ et al (2013) involved the use of a programmable freezer to subject the testicular fragments of mice to slow freezing. After the fragments passed through the equilibrium solution at 4°C, they were subjected to a temperature reduction of -1°C minute -1 until the temperature reached 0°C, and this temperature was maintained for 5 minutes.…”
Section: Cryopreservation Methods Of Testicular Tissuementioning
confidence: 99%